Study on the Model of Lesson Study-Based Handicraft Job Trainingin ECO Green Park Kota Batu - Zahro, Siti; ., Titi Mutiara Kiranawati (Journal of Education and Vocational Research, 2015)
The aim of this research is to provide information about the model of lesson study-based handicraft job training among the employees of ECO Green Park in guiding the visitors in their workplace. The research method applied was a descriptive method with a qualitative approach. Meanwhile, the population involved in this research was the employees of ECO Green Park in Department of Marketing, Fun and Game, Animal, Science Center, Chief Accounting, Public Area, gardener, Engineering and F&B. The type of sample used was a random sampling with the involvement of 65 persons. The technique in collecting data was conducted through questionnaire, interview and observation. The data analysis used here was in the form of a frequency distribution with an SPSS program for Windows version 21. The result of this research then shows a need of the employee for training materials to support their work. In addition, training facilities to support the achievement of training implementation and strategy in delivering the training materials are deemed essential to be a concern. Meanwhile, the evaluation of the training program was performed using the Kirkpatrick model highly suitable to measure the effectiveness of the training program at ECO Green Park.